Pengaruh Daya Tarik Dan Media Sosial Terhadap Keputusan Berkunjung Di Agrowisata Telaga Madiredo - Sari, Anis Widia; Slamet, Afi Rachmat; Dianawati, Eris (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract  This research aims to find out whether attractiveness and social media have an influence on tourists' decisions to visit Madiredo Lake Agrotourism which is located in Madiredo Village, Pujon District, Malang Regency. This research method uses quantitative methods. The population in this study was the people of Malang Raya who visited the Madiredo Lake Agrotourism. Using a sample using the Slovin formula, 99 respondents were obtained. In this research, the technique used was non-probability sampling. Non-probability sampling method involves selecting elements from the population without using a random process. This research shows that attractiveness and social media  have a significant influence on visitors' decision to visit Telaga Madiredo Agrotourism. Keywords: Social Media Marketing, E-WOM, Brand Experience, and Purchase Decision